2010
DOI: 10.1016/s1875-4597(10)60044-6
|View full text |Cite
|
Sign up to set email alerts
|

Tongue Traction is as Effective as Jaw Lift Maneuver for Trachlight-guided Orotracheal Intubation

Abstract: The tongue traction maneuver is as good as the jaw lift maneuver with regard to the success rate and time taken for Trachlight-guided orotracheal intubation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…[11] Lightwand has also been included in the difficult airway algorithm limb of American Society of Anesthesiologists. [12] Although tongue traction manoeuvre has been found to be as effective as the jaw lift manoeuvre,[13] we studied the jaw lift manoeuvre versus combined tongue and jaw lift manoeuvre as one of the studies has found that the oropharyngeal clearance was better with the combined manoeuvre for fibreoptic guided intubation. [14]…”
Section: Discussionmentioning
confidence: 99%
“…[11] Lightwand has also been included in the difficult airway algorithm limb of American Society of Anesthesiologists. [12] Although tongue traction manoeuvre has been found to be as effective as the jaw lift manoeuvre,[13] we studied the jaw lift manoeuvre versus combined tongue and jaw lift manoeuvre as one of the studies has found that the oropharyngeal clearance was better with the combined manoeuvre for fibreoptic guided intubation. [14]…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we placed the head in a slightly extended position and used the jaw lift maneuver. This maneuver lifts the tongue and epiglottis away from the posterior pharyngeal wall, thereby creating some space for the passage of gases [17] (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…In some cases of severe short mandible jaw lift maneuver cannot be sufficient. Association of mandible lift and tongue traction is indicated even if fibroscopy aid is used [17,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation